A Commentary on Perspectives of the Pet Effect: Exploring Public Awareness, Community Impact, and Public Policy Implications - Aubrey H. Fine; Zenithson Ng; Matthew P. Knight; Taylor Chastain Griffin; Lindsey Braun; Steven Feldman (Pets)
Today, the pet effect is a powerful symbol for advancing the understanding and acceptance of the human–animal bond in societal and policy arenas. The primary aim of this commentary is to clarify the concept of the “pet effect” and demonstrate how advocates for this bond can leverage its influence to promote meaningful change and inform public policy.